HbsAg SCREENING IN TEENAGERS IN SURABAYA BY USING RAPID TEST - Alamudi, M Yusuf; Hadi, M.Irfan; Kumalasari, Mei Lina Fitri (Preventif: Jurnal Kesehatan Masyarakat, 2018)
Background & Objective : Hepatitis B immunization in Indonesia generally observes early age group (infant) and still rarely observed in adolescence. Teenagers become very important because they will soon be married and have children. The purpose of this study was to determine hepatitis based on HBsAg by using Rapid test Material and Method: Analytical observational with cross sectional approach is done at Center for Health Studies Pondok Pesantren Universitas Nahdlatul Ulama Surabaya. The sample size was 54 adolescents using accidental sampling technique, with age between 19-20 years old. HbsAg examination using manual rapid test monotest. Result: The result of the research shows that the most respondents are female, 94.44% and male 5.56%. A manual rapid test monotest will show strips one for negative results and two for HbsAg positive results. Rapid test HBsAg Monotest showed negative results against 54 people. Conclusion: Based on the results of this study can be concluded that not found positive adolescent hepatitis based on HBsAg examination